Peripheral vision and perceptual asymmetries in young and older martial arts athletes and nonathletes - Muiños, M.; Ballesteros, S. (Attention, Perception, & Psychophysics, 2014)
The present study investigated peripheral vision (PV) and perceptual asymmetries in young and older martial arts athletes (judo and karate athletes) and compared their performance with that of young and older nonathletes. Stimuli were dots presented at three different eccentricities along the horizontal, oblique, and vertical diameters and three interstimulus intervals. Experiment 1 showed that although the two athlete groups were faster in almost all conditions, karate athletes performed significantly better than nonathlete participants when stimuli were presented in the peripheral visual field. Experiment 2 showed that older participants who had practiced a martial art at a competitive level when they were young were significantly faster than sedentary older adults of the same age. The practiced sport (judo or karate) did not affect performance differentially, suggesting that it is the practice of martial arts that is the crucial factor, rather than the type of martial art. Importantly, older athletes lose their PV advantage, as compared with young athletes. Finally, we found that physical activity (young and older athletes) and age (young and older adults) did not alter the visual asymmetries that vary as a function of spatial location; all participants were faster for stimuli presented along the horizontal than for those presented along the vertical meridian and for those presented at the lower rather than at the upper locations within the vertical meridian. These results indicate that the practice of these martial arts is an effective way of counteracting the processing speed decline of visual stimuli appearing at any visual location and speed.